Reliability and Validity of the Chinese Version of the Scale for Assessing the Stigma of Mental Illness in Nursing - Wang, Weiwei; Cui, Huixia; Zhang, Wenlu; Xu, Xiaoxiao; Dong, Hong (Frontiers in Psychiatry, 2021)
Abstract Background: The prevalence of mental illness continues to increase in China, but research on stigma is still in its infancy, and there are even fewer studies on stigma among nurses. A comprehensive, effective and reliable tool is needed to assess stigma in nursing so that it can be reduced or eliminated to improve nursing quality. This study aimed to translate a 20-item scale for assessing the stigma of mental illness in nursing into Chinese and evaluate its reliability and validity. Methods: An improved Brislin translation model was used to translate the nursing mental illness stigma assessment scale into Chinese. Content and face validity were determined by a panel of experts. A convenience sample of 501 nursing students was chosen. Confirmatory factor analysis, concurrent validity and known group comparison were used to evaluate the scale’s structural validity. The reliability was evaluated based on the internal consistency reliability and 2-week retest reliability. Results: The content validity index was 0.90. Confirmatory factor analysis showed that this study supported the three-factor model. The moderate correlation between the Chinese version of the Scale for Assessing the Stigma of Mental Illness in Nursing and the Perceived Devaluation Discrimination Scale suggested acceptable concurrent validity. Cronbach’s α (0.863) and the retest coefficient (0.839) were indicative of internal consistency. Conclusion: The Chinese version of the Scale for Assessing the Stigma of Mental Illness in Nursing has acceptable concurrent validity, marginal factor validity, and satisfactory reliability in China. Therefore, the three-factor structure of the Chinese scale should be considered. Relevance to clinical practice: The Chinese version of the Scale for Assessing the Stigma of Mental Illness in Nursing can be used to understand the degree of mental illness stigma in nursing.